COMPARATIVE STUDY OF RELIGIOUS MODERATION IN MUHAMMADIYAH AND PERSIS PESANTREN EDUCATION IN BANDUNG - Nisa, Ike Hilatun; Mubasirun, Mubasirun; Irkhami, Nafis; Dani ER, Fitria Erna (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: This study is motivated by the need to understand how pesantren education can shape positive social attitudes among students, particularly in the context of national awareness, tolerance, anti-violence, and acceptance of local culture. Purpose: The aim of this research is to analyze how the Muhammadiyah and Persatuan Islam (Persis) education systems in Bandung develop students’ attitudes toward national commitment, tolerance, anti-violence and anti-radicalism, as well as accommodative attitudes toward local culture. Method: The research employed a descriptive qualitative method with a case study approach, using in-depth interviews with teachers, pesantren principals, and students, along with participatory observation to obtain empirical data. Result: The results indicate that Muhammadiyah pesantrens emphasize the integration of moderation values into learning materials, social practices, and daily habituation as the main strategy for shaping social attitudes. Meanwhile, Persis pesantrens place more emphasis on religious ritual habituation, discussions on national issues, group activities, and social interactions as a means of internalizing religious moderation values. Both approaches are proven effective in fostering students’ awareness of their responsibilities as citizens, respect for differences, rejection of violence, and acceptance of local cultural diversity. Conclusion: The study concludes that value-based pesantren education, combined with the integration of social activities and ritual habituation, is highly effective in developing moderate social attitudes among students. Implication: These findings provide practical implications for the development of pesantren curricula and character education strategies that are contextual, adaptive, and relevant to the multicultural socio-cultural realities of Indonesian society.